Organizational Changes in Adopting Agile Approaches: A Systematic Literature Review. - Perides, Maria Paula Novakoski; Vasconcellos, Liliana (Journal of Applied Behavioral Science, 2025)
Although agile approaches to project management were originally developed for use by small software development teams, agile methods quickly began to be used by entire department processes and, in some cases, to the entire organization. Despite this quick adoption, there is a lack of studies seeking a better understanding of the changes that an organization needs to carry out for agile implementation at the organizational level. Therefore, a systematic literature review was conducted to organize and synthesize knowledge in this field. The main changes reported by these studies were consolidated into four major dimensions, that together, provided a consolidated view on the topic. In addition to contributing to the theory of agile approaches, it is also intended that this research will support the organizations that plan to undertake this journey of transformation, helping them plan the actions needed to achieve the desired results more consistently.